Precision Medicine in Ossiculoplasty. Issue 2 (February 2021) - Mukherjee, Payal; Cheng, Kai; Chung, Johnson; Grieve, Stuart M.; Solomon, Michael; Wallace, Gordon
Abstract : Introduction: Long term results of ossiculoplasty surgery are considered poor with displacement and extrusion amongst the common reasons for failure. Application of 3Dimensional (3D) printing may help overcome some of these barriers, however digital methods to attain accurate 3D morphological studies of ossicular anatomy are lacking, exacerbated by the limitation of resolution of clinical imaging. Methods: 20 human cadaveric temporal bones were assessed using micro computed tomography (CT) imaging to demonstrate the lowest resolution required for accurate 3D reconstruction. The bones were then scanned using conebeam CT (125 μm) and helical CT (0.6 mm). 3D reconstruction using clinical imaging techniques with microCT imaging (40 μm resolution) as a reference was assessed. The incus was chosen as the focus of study. Two different methods of 3D printing techniques were assessed. Results: A minimum resolution of 100 μm was needed for adequate 3D reconstruction of the ossicular chain. Conebeam CT gave the most accurate data on 3D analysis, producing the smallest mean variation in surface topography data relative to microCT (mean difference 0.037 mm, p  < 0.001). Though the incus varied in shape in between people, paired matches were identical. Thus, the contralateral side can be used for 3D printing source data if the ipsilateral incus is missing. Laser based 3D printing was superior to extrusion based printing to achieve the resolution demands for 3D printed ossicles. Conclusion: Resolution of modern imaging allows 3D reconstructions and 3D printing of human ossicles with good accuracy, though it is important to pay attention to thresholding during this process.